High-κ SrTiO3 thin film as gate dielectric of a solution processed SnO2 thin film transistor. (1st March 2023) - Acharya, Vishwas; Pal, Nila; Pandey, Utkarsh; Yadav, Akhilesh Kumar; Suthar, Mukesh; Roy, Pradip Kumar; Biring, Sajal; Pal, Bhola N.
Abstract: High dielectric constant (high-κ) gate insulating material is an essential component for low operating voltage thin film transistor (TFT) fabrication. Among different high-κ materials, a number of perovskite oxides are widely studied due to their unusually high dielectric constant. Out of them, strontium titanate (SrTiO3 ) is a well-known perovskite oxide material that has both good insulating behaviors with a very high-κ value. This work demonstrated the SrTiO3 thin film deposition by simple solution processed technique and its application for sol-gel derived SnO2 TFT fabrication. Although this SnO2 TFT can be operated within a low voltage range (<2 V) due to the high-κ value of SrTiO3 thin film, the device can be operating in the high voltage range (>15 V) as well because of its high breakdown voltage. Experimental data of this study indicates, in the low voltage range (<2 V), both output and transfer characteristics of the devices are hysteresis free. However, in the higher voltage range (>5 V), TFT characteristics show some hysteresis. An optimized TFT has carrier mobility ∼0.20 cm 2 /V.s. with an On/Off ratio of 2.3 × 10 4 in the low operating voltage range (<2 V) range. Whereas, carrier mobility is reduced a bit in the higher voltage range with a lower On/Off ratio due to the interface charge trapping.